Legal protection to Making Crafts Gerabah (Boso Mare) traditional knowledge copyright in The Mare Island, Town of Tidore Islands, Indonesia - M.Hum, Fatma Laha (Penerbit Universiti Kebangsaan Malaysia, 2019)
Research Concerning, Legal Protection to Making Crafts Gerabah (Boso Mare) Traditional Knowledge Copyright in the Mare Island, Town of Tidore Islands, focused on the craft Gerabah (Boso Mare) mechanism. This research is to (1) know the extent of legal protection to making craft Gerabah (Boso Mare) traditional knowledge copyright in the Mare Island, Town of Tidore Islands (2) knowing Mare Island people’s understanding of making craft Gerabah (Boso Mare) as traditional knowledge copyright. The research was conducted in Mare Island community. This type of research is normative with data collection techniques through field and literature study. Sources of data obtained in the form of primary and secondary data. Data analysis technique used is qualitative descriptive analysis. The results show that the people of Mare Island do not know about the importance of legal protection to making crafts Gerabah (Boso Mare) as traditional knowledge, the community does not know the registration procedure to register the craft Gerabah (Boso Mare) to the Directorate General of Intellectual Property Rights and the Regional Office of the Ministry of Law and Human Rights of North Maluku. Lack of socialization from Local Government so that people think that craft Gerabah (Boso Mare) hard to imitate, people believe that only the people of Mare Island alone can make crafts Gerabah (Boso Mare). In addition, without registered craft Gerabah (Boso Mare) products still sold in the market. Legal protection to making crafts Gerabah (Boso Mare) the effective participation of all components such as Local Government, Village Government and related agencies and local communities, especially the craftsmen Gerabah (Boso Mare).